Net base fiber reinforced ceramic matrix composite material as well as preparation method and application thereof
By preparing the interface layer on the prefabricated mesh fiber and combining impregnation and temperature pressing processes, the problems of long densification cycle and high cost of ceramic matrix composite materials are solved, and the gradient-free impregnation of ceramic slurry and the improvement of fiber volume fraction are achieved, the material densification efficiency is improved, and the preparation cycle is shortened.
Patent Information
- Application Number
- CN202510555434.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-07-04
AI Technical Summary
In the prior art, the ceramic matrix composite material has a long densification cycle and high cost, and the ceramic slurry impregnated fiber preform has a density gradient and it is difficult to produce the slurry impregnated fiber process.
The mesh fiber is used as the reinforcement body, and the gradient impregnation of the ceramic slurry is achieved through the "impregnation + temperature pressure" process, and the fiber volume fraction is increased and the net size molding is formed. The preparation method includes preparing an interface layer on the mesh fiber prefabricated body, impregnating the water-based ceramic slurry and phenolic resin solution, and then compressing and solidifying in the mold, and reacting through high-temperature cracking and melt-silicon seepage.
The non-gradient impregnation of ceramic slurry in the fiber reinforcement was achieved, the fiber volume fraction increased from 8 to 10% to 20 to 30%, the material densification efficiency was improved, the preparation cycle was shortened, and the cost was reduced.
Smart Images

Figure CN120247575A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic matrix composites, and particularly relates to a reticulated fiber reinforced ceramic matrix composite, a preparation method thereof and an application thereof. Background Art
[0002] Continuous fiber reinforced silicon carbide ceramic matrix composites (CMC-SiC) are a kind of composites with carbon fiber or silicon carbide fiber preforms as the reinforcement and SiC ceramic as the matrix. They have the characteristics of light weight, high temperature resistance, oxidation resistance, high specific stiffness, insensitivity to cracks, wear resistance, etc., and are widely used in aerospace thermal protection components, aerospace hot end components, carbon ceramic brake discs, and photovoltaic thermal field components. The SiC matrix of CMC-SiC is usually prepared by chemical vapor infiltration (CVI). However, the CVI-SiC process has high costs and a long cycle, which has been restricting the rapid batch production and low-cost application of CMC-SiC in civilian products.
[0003] In order to improve the densification efficiency of the SiC matrix, researchers have used precursor infiltration pyrolysis (PIP), molten silicon reaction infiltration (RMI), or composite processes such as "CVI+PIP" and "PIP+RMI" for the densification of the SiC matrix. The densification cycle of the matrix has been shortened, but the cost performance is not ideal. Further, some researchers have tried to use the slurry infiltration process (SI) to introduce SiC slurry into the fiber preform. If successful, this can greatly shorten the densification cycle of the SiC matrix. However, during the slurry infiltration process, it is difficult to introduce the slurry into the fiber preform, or there is a large density gradient between the center and the surface layer of the fiber preform during slurry infiltration. This not only causes the material to have a "hollow core" and extremely low strength, but also makes the technical route of using slurry infiltration for matrix densification stagnate without progress. In the prior art, the method of using a syringe injection method to introduce the slurry into the preform is tried to solve the problem that it is difficult to thoroughly infiltrate the impregnating material in the center part of the fiber and reduce the material density gradient. However, this process is difficult to achieve large-scale production, and batch production is still a problem. Summary of the Invention
[0004] Aiming at the deficiencies in the above background art, the present invention mainly solves the problems in the prior art such as the long densification cycle of the ceramic matrix composite matrix, high costs, density gradient in the impregnation of ceramic slurry into the fiber preform, and difficulty in batch production of the slurry impregnation fiber process. The present invention provides a reticulated fiber reinforced ceramic matrix composite, a preparation method thereof and an application thereof. This reticulated fiber reinforced ceramic matrix composite uses reticulated fibers as the reinforcement, and realizes gradient-free impregnation of ceramic slurry, improvement of fiber volume fraction and net size forming through the "impregnation + warm pressing" process. Its fiber volume fraction is increased from 8-10% to 20-30%. The finally obtained matrix is composed of a ceramic powder phase, an RMI-SiC phase, and a free silicon phase. The phases are evenly distributed, there is no density gradient in the thickness direction, and it is dense.
[0005] The first object of the present invention is to provide a method for preparing a fibrous web-reinforced ceramic matrix composite, comprising the following steps: Prepare an interface layer on the fibrous web preform to obtain a fibrous web preform with an interface layer; Prepare an aqueous ceramic slurry; Immerse the fibrous web preform with an interface layer into the aqueous ceramic slurry to obtain an intermediate one; When preparing the intermediate one, during the impregnation process, the fibrous web preform with an interface layer is repeatedly impregnated with the aqueous ceramic slurry for multiple times; The volume fraction of the ceramic powder in the aqueous ceramic slurry is 20-40 vol%, and the solid content is 5-30 wt.%; the size of the ceramic powder is micron powder or sub-micron powder; Immerse the phenolic resin solution into the intermediate one to obtain an intermediate two; Place the intermediate two in a mold, and after compressing its thickness to 50%-65% by applying pressure, carry out curing to obtain an intermediate three; Among them, the curing process includes: heating from 40-60°C to 130-160°C at a rate of 8-12°C / min, and then maintaining the temperature and pressure for 120-180 min; when preparing the intermediate three, the applied pressure is 1-5 MPa; Embed the intermediate three in silicon material, and under vacuum, successively carry out high-temperature pyrolysis and molten silicon infiltration reaction to obtain the fibrous web-reinforced ceramic matrix composite; Among them, the interface layer is a pyrolytic carbon interface layer; The aqueous ceramic slurry is prepared from ceramic powder, and the ceramic powder includes one or more of carbides MeC, nitrides MeN, and borides MeB2, where Me is Hf, Zr, Ta, Nb, or Ti; The high-temperature pyrolysis temperature is 800-1000°C, and the temperature is maintained for 120-180 min; The temperature of the molten silicon infiltration reaction is 1450-1550°C, and the temperature is maintained for 120-180 min.
[0006] Preferably, the mass fraction of the phenolic resin in the phenolic resin solution is 10-50 wt%.
[0007] Preferably, the impregnation process successively adopts vacuum impregnation and pressure impregnation.
[0008] Preferably, the thickness of the interface layer is 100-1000 nm.
[0009] The fibrous web preform is prepared by forming a web of carbon fibers or silicon carbide fibers using an air-laid machine.
[0010] Preferably, the fibrous preform with an interface layer is obtained by depositing a pyrolytic carbon interface layer on the fibrous preform by chemical vapor infiltration; Prepare an aqueous ceramic slurry, including: mixing ceramic powder, water and sodium carboxymethyl cellulose, and ball milling for 2 - 6 h to obtain the aqueous ceramic slurry; wherein, the addition amount of sodium carboxymethyl cellulose is 1 - 2 wt.% of the water amount.
[0011] The second object of the present invention is to provide a fibrous preform reinforced ceramic matrix composite.
[0012] The third object of the present invention is to provide an application of a fibrous preform reinforced ceramic matrix composite in a heat-resistant component.
[0013] Compared with the prior art, the beneficial effects of the present invention are: The present invention provides a fibrous preform reinforced ceramic matrix composite, its preparation method and application. The present invention uses a fibrous preform as the reinforcement, and through the "impregnation + warm pressing" process, realizes the non-gradient impregnation of the ceramic slurry, the increase of the fiber volume fraction and the net-size forming. Its fiber volume fraction is increased from 8 - 10% to 20 - 30%. The pore size is large and the pores are interconnected, providing a smooth channel for the impregnation of the slurry. It can not only smoothly reach the core of the fibrous preform with the slurry, but also greatly reduce the density gradient of the slurry impregnation; the finally obtained matrix is composed of a ceramic powder phase, an RMI-SiC phase and a free silicon phase. The phases are evenly distributed, there is no density gradient in the thickness direction, and it is dense.
[0014] The present invention uses the warm pressing process to compress the thickness of the fibrous preform reinforced body impregnated with the slurry. While increasing the fiber volume fraction, it also further densifies the matrix; in the mold, the phenolic resin is cured by heat, which can realize the integrated forming of the fibrous preform (intermediate) component, greatly improving the material forming efficiency, and providing a carbon source for the subsequent molten reaction infiltration of silicon; the impregnated aqueous ceramic slurry can be formulated in components to realize the composition design of the matrix; the high-temperature pyrolysis and molten silicon infiltration reaction processes can further reduce the cycle and cost of matrix densification. Description of the Drawings
[0015] Figure 1 is the process route diagram of the preparation method of the present invention.
[0016] Figure 2 is the microscopic SEM photo of the fibrous preform selected by the present invention.
[0017] Figure 3 is the cross-sectional view of the fibrous preform reinforced ceramic matrix composite prepared by the present invention and the enlarged microscopic SEM photo of the cross-sectional center.
[0018] Figure 4It is the enlarged microscopic BSE photograph of the cross-section center of the web-shaped fiber-reinforced ceramic matrix composite prepared by the invention and the composition identification.
[0019] Figure 5 It is the cross-sectional view and the enlarged microscopic SEM photograph of the cross-section center of the web-shaped fiber-reinforced RMI-SiC matrix composite prepared in Comparative Example 1. Specific embodiments
[0020] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings, but the specific embodiments cited do not limit the present invention.
[0021] The object of the present invention is to provide a web-shaped fiber-reinforced ceramic matrix composite, its preparation method and application, so as to solve the problems in the prior art such as the long densification period of the ceramic matrix composite matrix, high cost, density gradient in the impregnation of ceramic slurry into the fiber preform, and difficulty in mass production of the slurry impregnation fiber process.
[0022] The web-shaped fiber-reinforced ceramic matrix composite provided by the present invention mainly uses web-shaped fibers as the reinforcement, and realizes the gradient-free impregnation of ceramic slurry, the increase of fiber volume fraction and net-size forming through the "impregnation + warm pressing" process. Its fiber volume fraction is increased from 8-10% to 20-30%. The finally obtained matrix is composed of a ceramic powder phase, an RMI-SiC phase, and a free silicon phase. The phases are evenly distributed, there is no density gradient in the thickness direction, and it is dense.
[0023] In order to achieve the above object, the first aspect of the present invention provides a preparation method of a web-shaped fiber-reinforced ceramic matrix composite, as shown in Figure 1 shown, including the following steps: S1. Prepare an interface layer on the web-shaped fiber preform to obtain a web-shaped fiber preform with an interface layer; Prepare an aqueous ceramic slurry; Among them, the interface layer is a pyrolytic carbon interface layer; The aqueous ceramic slurry is prepared from ceramic powder. The ceramic powder includes one or more of carbides, nitrides, and borides; the carbides are mainly silicon carbide, and refractory metal carbides such as MeC, where Me is Hf, Zr, Ta, Nb or Ti, the nitrides are mainly silicon nitride and refractory metal nitrides, such as MeN, where Me is Hf, Zr, Ta, Nb or Ti, and the borides are mainly refractory metal borides such as MeB2, where Me is Hf, Zr, Ta, Nb or Ti.
[0024] The volume fraction of the ceramic powder in the aqueous ceramic slurry is 20-40 vol%, and the solid content is 5-30 wt.%; the size of the ceramic powder is micron powder or sub-micron powder.
[0025] The thickness of the interface layer is 100 - 1000 nm; the thickness of the pyrolytic carbon interface prepared for the fibrous preform of the web in the present invention is 100 - 1000 nm, which is beneficial to reducing the damage to the web fibers in the subsequent molten reaction silicon infiltration process and is also beneficial to improving the fracture toughness of the composite material.
[0026] The fibrous preform of the web is prepared by using an air-laying machine to lay carbon fibers or silicon carbide fibers into a web.
[0027] The fibrous preform of the web with an interface layer is prepared by chemically vapor infiltrating a pyrolytic carbon interface layer onto the fibrous preform of the web; Prepare an aqueous ceramic slurry, including: mixing ceramic powder, water and sodium carboxymethyl cellulose, and ball-milling for 2 - 6 h to obtain the aqueous ceramic slurry; wherein, the addition amount of sodium carboxymethyl cellulose is 1 - 2 wt.% of the water amount.
[0028] The ceramic powder in the aqueous ceramic slurry of the present invention can be formulated according to needs to realize the design of the matrix composition and achieve the purpose of modification such as wear resistance, thermal conductivity, wave absorption and penetration, high temperature resistance, etc.
[0029] With the design of the particle size and volume fraction of the ceramic slurry powder in the present invention, the suspension of the slurry is better, and the viscosity is less than 5 Pa·s, and the fluidity is better, which can further improve the impregnation efficiency of the aqueous ceramic slurry, and the impregnation uniformity is improved, which is beneficial to reducing the impregnation gradient.
[0030] S2. Immerse the fibrous preform of the web with an interface layer into the aqueous ceramic slurry to obtain Intermediate 1; Exemplarily, immerse the fibrous preform of the web with an interface layer into the aqueous ceramic slurry, and then dry it at 90 - 120 °C for 0.5 - 5 h to obtain Intermediate 1.
[0031] It should be noted that the immersion of the fibrous preform of the web with an interface layer into the aqueous ceramic slurry can be repeated 2 - 3 times; in the present invention, the ceramic slurry is repeatedly immersed 2 - 3 times, and it is not advisable to be too many. One is to ensure that the fiber reinforcement contains a high content of ceramic powder, and the other is to leave enough compression space for the subsequent warm pressing step.
[0032] The immersion process successively adopts vacuum impregnation and pressure impregnation; Among them, vacuum impregnation is to separately place the fibrous preform of the web and the aqueous ceramic slurry in a vacuum (pressure) tank, evacuate for 30 min, then immerse the fibrous preform of the web into the aqueous ceramic slurry, and continue to evacuate for 30 - 60 min; Pressure impregnation is to transfer it to a pressure tank after vacuum impregnation, add an air pressure of about 1 MPa for 30 min and then take it out.
[0033] When preparing Intermediate I, during the impregnation process, the fibrous preform with an interface layer is repeatedly impregnated with an aqueous ceramic slurry multiple times; S3. Impregnate the phenolic resin solution into Intermediate I to obtain Intermediate II; The mass fraction of the phenolic resin in the phenolic resin solution is 10 - 50 wt%.
[0034] Exemplarily, impregnate the phenolic resin solution into Intermediate I, and then place it in an oven at 55 ± 5 °C for 10 - 12 h to obtain Intermediate II.
[0035] In the present invention, the mass fraction of 10 - 50 wt% phenolic resin can first evenly disperse the phenolic solution into Intermediate I. After warm pressing and curing, it can reduce the warping deformation caused by uneven internal curing stress. Secondly, it can provide sufficient carbon source for the subsequent molten silicon infiltration reaction.
[0036] The impregnation process successively adopts vacuum impregnation and pressure impregnation.
[0037] Among them, for vacuum impregnation, Intermediate I and the phenolic resin solution are separately placed in a vacuum (pressure) tank. After evacuating for 30 min, Intermediate I is immersed in the phenolic resin solution, and then continue to evacuate for 30 - 60 min.
[0038] For pressure impregnation, after vacuum impregnation, transfer it to a pressure tank, add an air pressure of about 1 MPa for 30 min and then take it out.
[0039] S4. Place Intermediate II in a mold, and after compressing its thickness to 50% - 65% by applying pressure, carry out curing to obtain Intermediate III; The curing process includes: heating from 40 - 60 °C to 130 - 160 °C at a rate of 8 - 12 °C / min, and then maintaining the temperature and pressure for 120 - 180 min.
[0040] When preparing Intermediate III, the applied pressure is 1 - 5 MPa.
[0041] Exemplarily, place Intermediate II on a mold and a hot press, compress its thickness by 50% - 65% and then heat and cure to obtain Intermediate III; during the thickness compression process, the pressure of the hot press is 1 - 5 MPa. In the present invention, the lower pressure of the hot press can ensure that the ceramic slurry and phenolic solution impregnated into the fiber reinforcement are squeezed out, or the fiber reinforcement is fragmented.
[0042] The procedure during the heating and curing process is: heating from 50 °C to 150 °C at a rate of 10 °C / min, and then maintaining the temperature and pressure for 120 - 180 min. The heating and curing process in the present invention is beneficial to the stress release during curing, and there will be no deformation after forming, realizing net size forming.
[0043] S5. Embed the intermediate in silicon material. Under vacuum, through high-temperature pyrolysis and molten silicon infiltration reactions in sequence, a web-shaped fiber-reinforced ceramic matrix composite material is obtained; Among them, the high-temperature pyrolysis temperature is 800 - 1000 °C, and keep the temperature for 120 - 180 min; The molten silicon infiltration reaction temperature is 1450 - 1550 °C, and keep the temperature for 120 - 180 min.
[0044] It should be noted that the high-temperature pyrolysis and molten silicon infiltration reactions are carried out in one furnace charge. The molten silicon infiltration reaction process: one is to consume the previously introduced carbon source to form SiC; the second is that silicon combines or reacts with ceramic powder to further improve the strength of the material; the third is that free silicon fills the pores, which can reduce the porosity of the material to the lowest level; the fourth is that the high-temperature pyrolysis and molten silicon infiltration reactions are carried out in one furnace charge to further reduce the cycle and cost of matrix densification.
[0045] Among them, in the following examples, the silicon material used is pure silicon with a purity of 99% and an average particle size of 1 mm.
[0046] The second aspect of the present invention provides a web-shaped fiber-reinforced ceramic matrix composite material.
[0047] The third aspect of the present invention provides an application of the web-shaped fiber-reinforced ceramic matrix composite material in heat-resistant components.
[0048] It should be noted that the experimental methods used in the present invention are all conventional methods without special instructions; the reagents and materials used, without special instructions, can all be purchased on the market.
[0049] Example 1 A web-shaped fiber-reinforced ceramic matrix composite material is applied to the outer side of the quartz crucible for silicon-based single crystal furnace to support the crucible thermal field, the boat / paddle / furnace tube for diffusion furnace, etc. It is obtained by the following method: (1) Select a 15 mm thick web-shaped fiber preform, and use the chemical vapor infiltration method to prepare a pyrolytic carbon interface layer for 20 h to obtain a 100 nm thick pyrolytic carbon interface; mix silicon carbide powder, water and 2% sodium carboxymethyl cellulose in a ball mill jar and ball mill for 2 h to prepare a water-based silicon carbide ceramic slurry for standby; the particle size of the silicon carbide powder is 1000 - 1500 mesh, among which, the powder with 1000 mesh accounts for 60%, and the volume fraction of silicon carbide in the slurry is 30 vol%; (2) Place the web-shaped fiber preform with the interface and the water-based ceramic slurry separately in a vacuum (pressure) tank. After evacuating for 30 min, immerse the web-shaped fiber preform in the water-based ceramic slurry, and continue to evacuate for 50 min. Then transfer it to a pressure tank, add about 1 MPa of air pressure for 30 min and then take it out. Then dry it at 100 °C for 60 min to obtain Intermediate 1; among them, impregnate the ceramic slurry 2 times repeatedly, (3) Place Intermediate I and 50 wt% phenolic resin solution separately in a vacuum (pressure) tank. After evacuating for 30 min, immerse Intermediate I into the phenolic resin solution, and continue to evacuate for 50 min. Then transfer it to the pressure tank, apply a gas pressure of about 1 MPa for 30 min and then take it out. After that, place it in an oven at 55 ± 5 °C for 10 h to obtain Intermediate II; (4) Place Intermediate II on a mold and a hot press, compress its thickness by 50% to 7.5 mm with 1 MPa and then heat it for curing. The procedure during the heating and curing process is: heat from 50 °C to 150 °C at a rate of 10 °C / min, and then keep the temperature and pressure constant for 120 min to obtain Intermediate III; (5) Embed Intermediate III in silicon material, and carry out high-temperature pyrolysis and molten silicon infiltration reaction in one furnace under vacuum to obtain the final ceramic matrix composite material. The temperature for high-temperature pyrolysis is 800 °C and keep it for 120 min; the temperature for molten silicon infiltration reaction is 1500 ± 50 °C and keep it for 120 min.
[0050] The average flexural strength of the web tire fiber-reinforced ceramic matrix composite material prepared in Example 1 is 246.31 MPa; the measured thermal conductivity of the material is 165.767 W / (m·K).
[0051] Example 2 A web tire fiber-reinforced ceramic matrix composite material is applied to heat treatment in the back-end process of silicon-based semiconductors, MOCVD and other process chambers, such as edge rings, thin-wall support cylinders, MOCVD tray substrates, and other hot-end components used in rapid thermal processing furnaces. It is prepared by the following method: (1) Select a 10-mm-thick web tire fiber preform, and prepare a pyrolytic carbon interface layer for 50 h by chemical vapor infiltration method to obtain a 600-nm-thick pyrolytic carbon interface; mix silicon carbide powder, water and 2% sodium carboxymethyl cellulose in a ball mill for 2 h, and prepare an aqueous silicon carbide ceramic slurry for standby. The particle size of the silicon carbide powder is 1000 mesh, and the volume fraction of silicon carbide in the slurry is 40 vol%; (2) Place the web tire fiber preform with the interface and the aqueous ceramic slurry separately in a vacuum (pressure) tank. After evacuating for 30 min, immerse the web tire fiber preform into the aqueous ceramic slurry, and continue to evacuate for 30 min. Then transfer it to the pressure tank, apply a gas pressure of about 1 MPa for 30 min and then take it out. Then dry it at 100 °C for 60 min to obtain Intermediate I; among them, impregnate the ceramic slurry 2 times repeatedly, (3) Place Intermediate I and 10 wt% phenolic resin solution separately in a vacuum (pressure) tank. After evacuating for 30 min, immerse Intermediate I into the phenolic resin solution, and continue to evacuate for 60 min. Then transfer it to a pressure tank, apply a pressure of about 1 MPa for 30 min and then take it out. After that, place it in an oven at 55 ± 5 °C for 10 h to obtain Intermediate II; (4) Place Intermediate II on a mold and a hot press, compress its thickness by 65% to 3.5 mm with 5 MPa and then heat it for curing. The procedure during the heating and curing process is as follows: heat from 50 °C to 150 °C at a rate of 10 °C / min, and then keep the temperature and pressure for 180 min to obtain Intermediate III; (5) Embed Intermediate III in silicon material, and carry out high-temperature pyrolysis and molten silicon infiltration reaction in one furnace under vacuum to obtain the final ceramic matrix composite material. The temperature for high-temperature pyrolysis is 1000 °C and keep it for 180 min; the temperature for molten silicon infiltration reaction is 1500 ± 50 °C and keep it for 120 min.
[0052] The average flexural strength of the web tire fiber-reinforced ceramic matrix composite material prepared in Example 2 is 257.53 MPa; the measured thermal conductivity of the material is 174.558 W / (m·K).
[0053] Example 3 A web tire fiber-reinforced ceramic matrix composite material is applied to the field of friction and wear, such as brake disc and brake pad materials.
[0054] It is prepared by the following method: (1) Select a 50-mm-thick web tire fiber preform, and prepare a 1000-nm-thick pyrolytic carbon interface layer by chemical vapor infiltration for 100 h; mix silicon carbide powder, water and 2% sodium carboxymethyl cellulose in a ball mill for 2 h to prepare a water-based silicon carbide ceramic slurry for standby. The particle size of the silicon carbide powder is 1500 mesh, and the volume fraction of silicon carbide in the slurry is 20 vol%; (2) Place the web tire fiber preform with the interface and the water-based ceramic slurry separately in a vacuum (pressure) tank. After evacuating for 30 min, immerse the web tire fiber preform into the water-based ceramic slurry, and continue to evacuate for 60 min. Then transfer it to a pressure tank, apply a pressure of about 1 MPa for 30 min and then take it out. Then dry it at 100 °C for 60 min to obtain Intermediate I; among them, impregnate the ceramic slurry 3 times repeatedly, (3) Place Intermediate I and 40 wt% phenolic resin solution separately in a vacuum (pressure) tank. After evacuating for 30 min, immerse Intermediate I into the phenolic resin solution, and continue to evacuate for 30 min. Then transfer it to a pressure tank, apply a pressure of about 1 MPa for 30 min and then take it out. After that, place it in an oven at 55 ± 5 °C for 10 h to obtain Intermediate II; (4) Place intermediate two on a mold and a hot press, compress its thickness by 50% to 25 mm with 3 MPa, and then heat it up for curing. The procedure during the heating-up curing process is as follows: heat it up from 50 °C to 150 °C at a rate of 10 °C / min, and then keep the temperature and pressure constant for 180 min to obtain intermediate three; (5) Embed intermediate three in silicon material, and carry out high-temperature pyrolysis and molten silicon infiltration reaction in one furnace under vacuum to obtain the final ceramic matrix composite material. The temperature for high-temperature pyrolysis is 1000 °C and keep it for 120 min; the temperature for molten silicon infiltration reaction is 1500 ± 50 °C and keep it for 120 min.
[0055] The average flexural strength of the web tire fiber-reinforced ceramic matrix composite material prepared in Example 3 is 288.23 MPa; the dynamic friction coefficient is 0.36 - 0.48, and the wear rate ≤ 0.02×10 -7 cm 3 / N·m.
[0056] Example 4 A web tire fiber-reinforced ceramic matrix composite material is applied to the high-temperature wave-transparent hot end material of an aircraft. It is prepared by the following method: (1) Select a 5-mm-thick web tire fiber preform, prepare a pyrolytic carbon interface layer by chemical vapor infiltration for 40 h to obtain a pyrolytic carbon interface with an average thickness of 400 nm; and mix silicon nitride powder, water and 2% sodium carboxymethyl cellulose in a ball mill for 2 h to prepare a water-based silicon nitride ceramic slurry for standby. The particle size of the silicon nitride powder is 1000 - 1500 mesh, and the powder with 1000 mesh accounts for 60%. The volume fraction of silicon nitride in the slurry is 40 vol%; (2) Place the web tire fiber preform with the interface and the water-based ceramic slurry separately in a vacuum (pressure) tank. After evacuating for 30 min, immerse the web tire fiber preform in the water-based ceramic slurry, and continue to evacuate for 40 min. Then transfer it to a pressure tank, add a pressure of about 1 MPa for 30 min and then take it out. Then dry it at 100 °C for 60 min to obtain intermediate one; among them, impregnate the ceramic slurry 2 times repeatedly, (3) Place intermediate one and 25 wt% phenolic resin solution separately in a vacuum (pressure) tank. After evacuating for 30 min, immerse intermediate one in the phenolic resin solution, and continue to evacuate for 50 min. Then transfer it to a pressure tank, add a pressure of about 1 MPa for 30 min and then take it out. Then place it in an oven at 55 ± 5 °C for 10 h to obtain intermediate two; (4) Place intermediate two on a mold and a hot press, compress its thickness by 50% to 2.5 mm with 1 MPa, and then heat it up for curing. The procedure during the heating-up curing process is as follows: heat it up from 50 °C to 150 °C at a rate of 10 °C / min, and then keep the temperature and pressure constant for 180 min to obtain intermediate three; (5) Embed the intermediate in silicon material, and carry out high-temperature pyrolysis and molten silicon infiltration reaction in one furnace under vacuum to obtain the final ceramic matrix composite material. The temperature of high-temperature pyrolysis is 1000 °C for heat preservation for 120 min; the temperature of molten silicon infiltration reaction is 1500 ± 50 °C for heat preservation for 120 min.
[0057] The average flexural strength of the web tire fiber-reinforced ceramic matrix composite material prepared in Example 4 is 266.65 MPa; its dielectric constant and dielectric loss tangent value are 3.62 F / m and 4.31×10 -3 .
[0058] Example 5 A web tire fiber-reinforced ceramic matrix composite material is applied to the external thermal protection field of an aircraft, and it is prepared by the following method: (1) Select a 7-mm-thick web tire fiber preform, and prepare a pyrolytic carbon interface layer for 30 h by chemical vapor infiltration method to obtain a pyrolytic carbon interface with an average thickness of 300 nm; weigh the powder according to HfC:ZrB2:TiN = 2:1:1, then add water and 2% sodium carboxymethyl cellulose, and mix them in a ball mill for 2 h to prepare an aqueous ceramic slurry; (2) Place the web tire fiber preform with the interface and the aqueous ceramic slurry separately in a vacuum (pressure) tank. After evacuating for 30 min, immerse the web tire fiber preform in the aqueous ceramic slurry, and continue to evacuate for 50 min. Then transfer it to a pressure tank, add an air pressure of about 1 MPa for 30 min and then take it out. Then dry it at 100 °C for 60 min to obtain Intermediate 1; among them, impregnate the ceramic slurry 2 times repeatedly, (3) Place Intermediate 1 and 25 wt% phenolic resin solution separately in a vacuum (pressure) tank. After evacuating for 30 min, immerse Intermediate 1 in the phenolic resin solution, and continue to evacuate for 50 min. Then transfer it to a pressure tank, add an air pressure of about 1 MPa for 30 min and then take it out. Then place it in an oven at 55 ± 5 °C for 10 h to obtain Intermediate 2; (4) Place Intermediate 2 on a mold and a hot press, compress its thickness by 50% to 3.5 mm with 1 MPa and then heat it for curing. The procedure during the heating and curing process is: heat it from 50 °C to 150 °C at a rate of 10 °C / min, and then keep it warm and pressurized for 180 min to obtain Intermediate 3; (5) Embed Intermediate 3 in silicon material, and carry out high-temperature pyrolysis and molten silicon infiltration reaction in one furnace under vacuum to obtain the final ceramic matrix composite material. The temperature of high-temperature pyrolysis is 1000 °C for heat preservation for 120 min; the temperature of molten silicon infiltration reaction is 1500 ± 50 °C for heat preservation for 120 min.
[0059] The average flexural strength of the web tire fiber-reinforced ceramic matrix composite prepared in Example 5 is 236.55 MPa; after atmospheric plasma ablation at 2050 °C for 900 s, the composite material exhibits excellent ultra-high temperature ablation resistance, with a mass ablation rate of less than 1.0×10 -3 g / s and a linear ablation rate of less than 2.15×10 -3 mm / s.
[0060] Comparative Example 1 A three-dimensional needled carbon fiber preform-reinforced silicon carbide ceramic matrix composite (3DN C f / SiC), the preparation method includes: Using a three-dimensional needled carbon fiber preform as the reinforcement, a pyrocarbon interface layer is prepared. The preparation method and thickness of the interface layer are the same as those in Example 1; and it is placed in a prepared silicon carbide powder slurry for repeated impregnation. The impregnation method, number of repetitions, and the silicon carbide slurry used are the same as those in Example 1; (2) Then impregnate with phenolic carbon. The concentration and method of impregnating phenolic are the same as those in Example 1; (3) The methods of pyrolysis and molten silicon infiltration reaction are the same as those in Example 1.
[0061] (4) Machine the surface.
[0062] The average flexural strength of the 3DN C f / SiC prepared in Comparative Example 1 is 134.10 MPa; the thermal conductivity is 150.760 W / (m·K).
[0063] Comparative Example 2 Using a two-dimensional carbon fiber cloth ply as the reinforcement, matrix densification is carried out by the CVI method to obtain a two-dimensional ply carbon fiber-reinforced SiC composite material (2D C f / SiC), the preparation method includes: Using a two-dimensional carbon fiber cloth ply as the reinforcement, an interface layer is prepared. The preparation method and interface layer thickness are the same as those in Example 1; using chemical vapor deposition (CVI) method for matrix densification; demold and machine the surface. The average flexural strength of the web tire fiber-reinforced ceramic matrix composite prepared in Comparative Example 2 is 406.19 MPa.
[0064] The relevant preparation cycle analysis and performance tests are carried out on the ceramic matrix composites in the above examples and comparative examples, as described below: The preparation cycle accounting is shown in Table 1. Table 1 Preparation cycle accounting table for different processes
[0065] As shown in Table 1, the current three-dimensional needled carbon fiber preform-reinforced silicon carbide-based ceramic matrix composite (3DN C fThe preparation cycle of the ordinary carbon fiber reinforced silicon carbide ceramic matrix composite material (2D C / SiC) is 9 days, while the preparation cycle of the reticulated fiber reinforced ceramic matrix composite material of the present invention is about 7 days, shortening the preparation cycle by 22%; the preparation cycle of the ordinary carbon fiber reinforced silicon carbide ceramic matrix composite material (2D C f / SiC) is 36.5 days, and the preparation cycle of the present invention is shortened by 80%. It can be seen that the preparation method of the present invention can greatly shorten the preparation cycle and improve the preparation efficiency.
[0066] (2)Flexural strength Using a universal testing machine, the flexural strength tests were carried out on the products prepared in Examples 1-5 and Comparative Examples 1-2 in accordance with ASTM-C1341−13S "Standard Test Method for Flexural Properties of Continuous Fiber-Reinforced Advanced Ceramic Composites1", as shown in Table 2.
[0067] Table 2 shows the flexural strength test results of the composite materials provided in Examples 1-5 and Comparative Examples 1-2
[0068] Referring to Table 2, it can be seen that the three-point flexural strength of the reticulated fiber reinforced ceramic matrix composite material prepared by the present invention is 1.76-2.14 times that of 3D NC f / SiC. This is because in 3D NC f / SiC, due to the slurry impregnation density gradient, there are more pores in the core of the material, resulting in the material not being dense enough and having lower strength. In addition, the three-point bending strength of the reticulated fiber reinforced ceramic matrix composite material prepared by the present invention is about 60%-70% of that of the 2D NC f / SiC process ceramic matrix composite material, indicating that due to the reasonable design of the thickness of the pyrolytic carbon interface layer in the present invention, during the molten silicon infiltration process, the damage of liquid silicon to carbon fibers is effectively hindered.
[0069] (3)Thermal conductivity test Using a laser thermal conductivity meter, the thermal conductivity tests were carried out on Examples 1-2 and Comparative Example 1 in accordance with ASTM E1461-13 "Standard Test Method for Thermal Diffusivity by the Flash Method", as shown in Table 3.
[0070] Table 3 shows the thermal conductivity test results of the composite materials provided in Examples 1-2 and Comparative Example 1
[0071] The formula for the thermal conductivity of the material is: λ=α·ρ·c Where, λ: thermal conductivity, unit W / (m·K); α: thermal diffusion coefficient mm 2 / s; ρ: density, unit Kg / m 3 ; c: specific heat capacity, unit: J / (Kg·K).
[0072] It can be seen from Table 3 that the thermal conductivity of the material is positively correlated with the density. The thermal conductivity of the mesh fiber reinforced ceramic matrix composite material prepared by the present invention is higher than that of 3DN C f / SiC materials, mainly 3DN C f / SiC has a low thermal conductivity due to the density gradient of slurry impregnation and the presence of many pores in the core of the material. The material is not dense enough and has a low density.
[0073] (4) Friction and wear test A small bench test machine was used to test the friction and wear properties of the material in Example 3. The braking process was carried out in accordance with the SAE-J2522 standard. After the friction test, the volume wear rate and mass wear rate were measured. The test method was: GB / T 5763-2008 "Brake Linings for Automobiles".
[0074] (5) Dielectric constant measurement The dielectric constant and dielectric loss tangent of the material in Example 4 were measured in accordance with GB / T 5594.4-2015 "Test methods for properties of structural ceramic materials for electronic components Part 4: Test methods for dielectric constant and dielectric loss tangent".
[0075] (6) Ablation measurement After the material in Test Example 5 was subjected to atmospheric plasma ablation at 2050° C. for 900 s, the mass ablation rate and the line ablation rate were measured.
[0076] Figure 2 This is a microscopic SEM photo of the web fiber preform provided in Example 1 of the present invention. It is observed that the fibers are combed into a web structure by airflow.
[0077] Figure 3 This is a cross-sectional view and a magnified microscopic SEM photograph of the cross-sectional center of the web fiber reinforced ceramic matrix composite material prepared in Example 2 of the present invention. It can be seen that the cross-sectional surface of the 5 mm thick material is dense, and there is no density gradient between the core and the surface.
[0078] Figure 4 This is an enlarged microscopic BSE photograph of the cross section center of the web fiber reinforced ceramic matrix composite material prepared in Example 2 of the invention and component identification, in which the fibers, silicon carbide components and silicon components can be clearly seen.
[0079] Figure 5This is a cross-sectional view and a magnified microscopic SEM photograph of the cross-sectional center of the web fiber reinforced RMI-SiC matrix composite material prepared in Comparative Example 1. It can be seen that there are many pores in the core, and there is a density gradient between the core and the surface of the material.
[0080] In summary, the present invention provides a mesh fiber reinforced ceramic matrix composite material and its preparation method and application, and realizes the non-gradient impregnation of ceramic slurry, the improvement of fiber volume fraction and net size molding through the "impregnation + temperature pressing" process. The matrix finally obtained is composed of ceramic powder phase, RMI-SiC phase and free silicon phase, each phase is evenly distributed, there is no density gradient in the thickness direction, and it is dense. Its preparation method is to first impregnate the prepared ceramic slurry into the mesh fiber and then dry it, then impregnate the phenolic resin solution into the mesh fiber, and press the mold to reduce the thickness, so that not only the fiber volume fraction is increased from 8~10% to 20~30%, but also the temperature is increased during the pressure holding process to solidify and form, and finally the material density and strength are improved by cracking and melt siliconization reaction. The present invention takes advantage of the low volume fraction of the mesh fiber to introduce the ceramic slurry into the fiber reinforcement, realizes the non-gradient impregnation of the ceramic slurry in the fiber reinforcement, and then realizes the doubling of the fiber volume fraction and net size molding through temperature and pressure curing, the matrix densification efficiency is greatly improved, and the preparation cycle is significantly shortened.
[0081] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation method of a net tire fiber-reinforced ceramic matrix composite material, characterized in that, It includes the following steps: Prepare an interface layer on the web tire fiber preform to obtain a web tire fiber preform with an interface layer; Prepare an aqueous ceramic slurry; Immerse the web tire fiber preform with an interface layer into the aqueous ceramic slurry to obtain Intermediate One; During the preparation of Intermediate One, during the immersion process, the web tire fiber preform with an interface layer is repeatedly immersed in the aqueous ceramic slurry for multiple times; The volume fraction of the ceramic powder in the aqueous ceramic slurry is 20 - 40 vol%, and the solid content is 5 - 30 wt.%; the size of the ceramic powder is micron powder or sub-micron powder; Immerse the phenolic resin solution in Intermediate One to obtain Intermediate Two; Place Intermediate Two in a mold, and after compressing its thickness to 50% - 65% by applying pressure, cure it to obtain Intermediate Three; Among them, the curing process includes: heating from 40 - 60 °C to 130 - 160 °C at a rate of 8 - 12 °C / min, and then maintaining the temperature and pressure for 120 - 180 min; when preparing Intermediate Three, the applied pressure is 1 - 5 MPa; Embed Intermediate Three in silicon material, and under vacuum, successively carry out high-temperature pyrolysis and molten silicon infiltration reaction to obtain the web tire fiber-reinforced ceramic matrix composite; Among them, the interface layer is a pyrolytic carbon interface layer; The aqueous ceramic slurry is prepared from ceramic powder, and the ceramic powder includes one or more of carbide MeC, nitride MeN, and boride MeB2, where Me is Hf, Zr, Ta, Nb, or Ti; The high-temperature pyrolysis temperature is 800 - 1000 °C, and the heat preservation is 120 - 180 min; The molten silicon infiltration reaction temperature is 1450 - 1550 °C, and the heat preservation is 120 - 180 min.
2. The preparation method of the net tire fiber-reinforced ceramic matrix composite material according to claim 1, characterized in that, The mass fraction of the phenolic resin in the phenolic resin solution is 10 - 50 wt%.
3. The preparation method of the fiber-reinforced ceramic matrix composite material for a net tire according to claim 1, characterized in that, The immersion process successively adopts vacuum immersion and pressure immersion.
4. The preparation method of the fiber-reinforced ceramic matrix composite material for the net tire according to claim 1, characterized in that, The thickness of the interface layer is 100 - 1000 nm; The web tire fiber preform is prepared by using an air-laying machine to lay carbon fiber or silicon carbide fiber into a web; 5. The preparation method of the fiber-reinforced ceramic matrix composite material for the net tire according to claim 1, wherein, The web tire fiber preform with an interface layer is obtained by chemically vapor infiltrating a pyrolytic carbon interface layer on the fiber of the web tire fiber preform; Prepare the aqueous ceramic slurry, including: mixing ceramic powder, water, and sodium carboxymethyl cellulose, and ball-milling for 2 - 6 h to obtain the aqueous ceramic slurry; among them, the addition amount of sodium carboxymethyl cellulose is 1 - 2 wt.% of the water amount.
6. A web tire fiber-reinforced ceramic matrix composite prepared by the method according to any one of claims 1 - 5.
7. An application of the web tire fiber-reinforced ceramic matrix composite according to claim 6 in a heat-resistant component.
Citation Information
Cited By
Preparation method of silicon carbide ceramic-based composite material with internal embedded hole defects
CN121202591A